Effectiveness of Zoom-Based Menstrual Health Education in Improving Adolescents' Knowledge of Dysmenorrhea Management: A Quasi-Experimental Study - Adib Fattah Decky Ardhana; Devi Permata Sari (Journal of Islamic Studies and Education, 2026)
Dysmenorrhea is a common menstrual disorder among adolescents that negatively affects daily activities, academic performance, and quality of life. However, many adolescent girls lack adequate knowledge of dysmenorrhea and its evidence-based management. This study evaluated the effectiveness of Zoom-based health education in improving adolescents' knowledge of dysmenorrhea. A quasi-experimental one-group pretest-posttest design was conducted among 41 female high school students selected through purposive sampling. Participants attended a 90-minute synchronous Zoom-based educational session covering menstrual physiology, dysmenorrhea, risk factors, pharmacological and non-pharmacological management, and self-care practices. Knowledge was assessed using a structured questionnaire before and after the intervention, and descriptive statistics were used to summarize the findings. Before the intervention, 30 participants (73.2%) had poor knowledge, 7 (17.1%) had fair knowledge, and 4 (9.7%) had good knowledge. Following the intervention, the proportion of participants with poor knowledge decreased to 11 (26.8%), while those with good knowledge increased to 22 (53.7%). Participants also reported that the interactive online learning environment, multimedia materials, and discussion sessions improved their understanding and corrected misconceptions regarding menstrual pain management. These findings indicate that Zoom-based health education effectively enhances adolescents' knowledge and menstrual health literacy. Integrating digital menstrual health education into school health promotion programs may strengthen self-care practices and improve adolescent reproductive health outcomes.